2009
DOI: 10.1002/bem.20528
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extremely low‐frequency magnetic fields on the oviposition of Drosophila melanogaster over three generations

Abstract: The aim of this study was to determine the effects of an extremely low-frequency 50 Hz magnetic field (ELFMF) on the oviposition and development of Drosophila melanogaster. The results show that exposure of D. melanogaster females of generation P and all the development stages of generation F1 to an ELFMF weakened the oviposition of these insects in their subsequent generations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
8
1
Order By: Relevance
“…The occurrence of genotoxicity dropped in the appliance, which is good because it is more important and related to daily life. No effect was detected on fecundity in our test, while in D. melanogaster females, Gonet et al [ 41 ] reported egg reduction by a 50 Hz magnetic field. Panagopoulos [ 42 ] demonstrated the influence of microwaves from mobile telephone radiation on the ovary, and hence reproduction ability [ 43 , 44 , 45 ], and Kesari et al [ 46 ] warned the risk of sperm decrease of males using the Wister rat under mobile-phone level radiation.…”
Section: Discussioncontrasting
confidence: 64%
“…The occurrence of genotoxicity dropped in the appliance, which is good because it is more important and related to daily life. No effect was detected on fecundity in our test, while in D. melanogaster females, Gonet et al [ 41 ] reported egg reduction by a 50 Hz magnetic field. Panagopoulos [ 42 ] demonstrated the influence of microwaves from mobile telephone radiation on the ovary, and hence reproduction ability [ 43 , 44 , 45 ], and Kesari et al [ 46 ] warned the risk of sperm decrease of males using the Wister rat under mobile-phone level radiation.…”
Section: Discussioncontrasting
confidence: 64%
“…Embryonic development of invertebrate and vertebrate species can be disturbed by a variety of chemical and environmental stressors; therefore, it is not surprising that the possible influence on ELF EMF on embryogenesis was a subject of several studies (e.g. MA and CHU, 1993;MICHEL and GUTZEIT, 1999;GRAHAM et al, 2000;GONET et al, 2009;PANAGOPOULOS et al, 2013;DIMITRIJEVIĆ et al, 2014). Gametogenesis (especially oogenesis) and embryogenesis are a far more sensitive biological phase than the later developmental stages in all animals.…”
Section: Discussionmentioning
confidence: 99%
“…Gametogenesis (especially oogenesis) and embryogenesis are a far more sensitive biological phase than the later developmental stages in all animals. It was shown in experiments on D. melanogaster that ELF EMF exposure of developing follicles resulted in elimination of numbers of them, and a corresponding decrease in oviposition, while exposure of fertilized embryos (eggs) to the same fields did not cause a significant effect (PANAGOPOULOS and MARGARITIS, 2003;GONET et al, 2009). Similarly, we did not have significant differences between the control and the exposed group in early fecundity and egg-to-adult viability, when fertilized embryos were exposed to ELF EMF, but other studies with different experimental protocols detected a reduction in fecundity (GONET et al, 2009;PANAGOPOULOS et al, 2013;LI et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of EMF exposure on insect morphology, physiology and behavior have been proved previously. The EMF exposure induced changes in: mosquito egg hatching (Pan and Liu 2004 ), ovipositon in Drosophila (Gonet et al 2009 ), locomotor activity of desert locust and American cockroach (Wyszkowska et al 2006 , 2016 ) or antioxidant defense in Baculum extradentatum (Todorović et al 2012 ). EMF exposure has been also shown to induce a release of octopamine—an insect ‘stress hormone’ in American cockroach (Wyszkowska et al 2006 ), whereas the static electric field exposure elevated octopamine levels in Drosophila brain (Newland et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%